Analisis Hubungan Fasilitas Pelayanan Kesehatan Gigi dan Kegiatan Penambalan dan Pencabutan Gigi di Puskesmas - Andayasari, Lely (Jurnal Biotek Medisiana Indonesia, 2014)
Dental disease is widespread in Indonesian society. In Riskesdas 2013 reported 25.9% of Indonesias population of dental problems. The unmet dental health care facilities are among the factors that contribute to high oral and dental problems. Objective: to analyze the relationship between the availability of health care facilities with activities oral dental care (fillings and extractions) at the health center. The study was cross-sectional. The unit of analysis is all health centers in Indonesia, which has been registered in the Directorate General of Health Services Ministry of Health of Indonesia and operates before February 2011.Results of the analysis showed an association between the availability of dental health equipment with fillings and extractions activities OR 0.62; (0.41 to 094) and the p value of 0.024. There is a significant correlation between the activity of patched and tooth extraction services with medical supplies and drugs for completeness poly teeth in health centers and there is a significant relationship between service activities patched and extraction with the presence or absence UKGMD program at the health center. Provincial and district health authorities to improve the availability and completeness of medical equipment and dental filling material for dental poly in PHC.Keywords: Dental health facilities, RiskesdasÂ AbstrakPenyakit gigi dan mulut merupakan penyakit yang tersebar luas di masyarakat Indonesia. Pada Riskesdas 2013 dilaporkan 25,9% penduduk Indonesia bermasalah gigi. Belum terpenuhinya fasilitas pelayanan kesehatan gigi merupakan salah satu faktor yang berkontribusi pada tingginya masalah gigi dan mulut. untuk menganalisis hubungan ketersediaan fasilitas pelayanan kesehatan gigi dan mulut dengan kegiatan pelayanan kesehatan gigi (penambalan dan pencabutan gigi) di Puskesmas. Metode: Jenis penelitian adalah cross sectional. Unit analisis adalah seluruh Puskesmas di Indonesia yang telah terdaftar di Direktorat Jenderal Bina Upaya Kesehatan Kemenkes RI dan beroperasi sebelum Februari 2011. Analisis menunjukan adanya hubungan antara ketersediaan peralatan kesehatan gigi dan mulut dengan kegiatan penambalan dan pencabutan gigi OR 0,62; (0,41-094) dan p value 0,024. Adanya hubungan yang bermakna antara adanya kegiatan pelayanan tambal dan cabut gigi dengan kelengkapan alkes dan obat untuk poli gigi di Puskesmas serta terdapat hubungan yang bermakna antara kegiatan pelayanan tambal dan cabut gigi dengan ada-tidaknya program UKGMD di Puskesmas. Saran: Dinas kesehatan provinsi dan kabupaten untuk meningkatkan ketersediaan dan kelengkapan alat kesehatan dan bahan tambal gigi untuk poli gigi di Puskesmas.Kata kunci: Fasilitas kesehatan gigi, Riskesdas